Baromkeh : matamu di mataku - Ummu Hani Abu Hassan , 1983- (Kuala Lumpur, Malaysia : Utusan Publications & Distributors, 2008)
Prize winning novel in the 2007 Hadiah Sastera young adult literature contest of Kumpulan Utusan
"Pemenang kategori novel remaja" -- cover
Keywords: Malay fiction